GAYA BELAJAR DAN KOMPETENSI DITINJAU DARI TINGKAT JABATAN - ANGGIE DEA NILOVA, GIOVANA; NUGROHOSENO, DWIARKO (Jurnal Ilmu Manajemen (JIM), 2019)
At present the increasingly rapid business world requires a competent manager. The PDAM is a public sector company that is used as the right object of research for investigating how employees learn and develop in an effort to become competent managers. This research aims to analyze differences in learning styles and competencies of managers and non-managers of PDAM Delta Tirta Sidoarjo.This research is a type of comparative research using a quantitative approach with sampling techniques using purposive sampling. A total of 51 employees participated in this study, including 24 managers and 27 non-managers. Statistical analysis used in this research is Multivariate Analysis of Variance (MANOVA) with the assistance software SPSS 20.0. The results of this study indicate that there are differences in learning styles and competencies of managers and non-managers.